2020
DOI: 10.3390/nu12061871
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Stilbenes and Flavonoids is Linked to Reduced Risk of Obesity Independently of Fiber Intake

Abstract: Background: Polyphenol consumption is implicated in gut microbiome composition and improved metabolic outcomes, but it is unclear whether the effect is independent of dietary fiber. Methods: We investigated the links between (poly)phenol intake, gut microbiome composition (16s RNA) and obesity independently of fiber intake in UK women (n = 1810) and in a small group of UK men (n = 64). Results: (Poly)phenol intakes correlated with microbiome alpha diversity (Shannon Index) after adjusting for confounders and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…On the other hand, it may be due to the presence of compounds common in vegetables but not in fruits. This would exclude plant-based food components such as dietary fibre or polyphenols, which are found both in fruit and vegetables [44] and tend to be higher in fruits. We hypothesised that it could be dietary nitrate content, which has been related to improved cardiometabolic outcomes [45], increased nitric oxide production and altered inflammation and immune function [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it may be due to the presence of compounds common in vegetables but not in fruits. This would exclude plant-based food components such as dietary fibre or polyphenols, which are found both in fruit and vegetables [44] and tend to be higher in fruits. We hypothesised that it could be dietary nitrate content, which has been related to improved cardiometabolic outcomes [45], increased nitric oxide production and altered inflammation and immune function [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lachnospira was negatively correlated with PRT, NA, FE, VD, VB6, and VB12 intake ( rs = −0.38, −0.41, −0.39, −0.63, −0.42, −0.49, respectively). A previous study demonstrated that the relative abundance of Lachnospira was positively associated with vegetable intake [ 53 ], and that Lachnospira had a positive correlation with stilbene in an observational study [ 54 ]. Ingestion of a high-fat diet (HFD) induces oxidative stress and microbial dysbiosis, the latter playing an important role in the development of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In a coculture of adipocyte and macrophage system, piceatannol significantly reduced the release of TNF-α and monocyte chemoattractant protein-1 (MCP-1) [ 111 ]. Stilbene, flavonoid and total (poly)phenol intake was associated with higher gut microbiome diversity, an increase in butyrate producing organisms and 20–23% lower prevalence of obesity [ 112 ].…”
Section: Herbal and Dietary Supplementation For Weight Managementmentioning
confidence: 99%
“…Nutrients 2021, 13, x FOR PEER REVIEW 12 of 24 release of TNF-α and monocyte chemoattractant protein-1 (MCP-1) [111]. Stilbene, flavonoid and total (poly)phenol intake was associated with higher gut microbiome diversity, an increase in butyrate producing organisms and 20%-23% lower prevalence of obesity [112]. Mechanism of action: Piceatannol inhibits adipogenesis by inhibiting mitotic clonal expansion and lowering the protein levels of adipogenic transcription factors such as PPARγ and C/EBPα in 3T3-L1 cells in vitro.…”
Section: Curcuma Longamentioning
confidence: 99%